Get Tough, Get Toxic, or Get a Bodyguard: Identifying Candidate Traits Conferring Belowground Resistance to Herbivores in Grasses - Moore, Ben D.; Johnson, Scott N. (Frontiers in Plant Science, 2017)
Grasses (Poaceae) are the fifth-largest plant family by species and their uses for crops, forage, fibre and fuel make them the most economically important. In grasslands, which broadly-defined cover 40% of the Earth’s terrestrial surface outside of Greenland and Antarctica, 40-60% of net primary productivity and 70-98% of invertebrate biomass occurs belowground, providing extensive scope for interactions between roots and rhizosphere invertebrates. Grasses invest 50-70% of fixed carbon into root construction, which suggests roots are high value tissues that should be defended from herbivores, but we know relatively little about such defences. In this article, we identify candidate grass root defences, including physical (tough) and chemical (toxic) resistance traits, together with indirect defences involving recruitment of root herbivores’ natural enemies. We draw on relevant literature to establish whether these defences are present in grasses, and specifically in grass roots, and which herbivores of grasses are affected by these defences. Physical defences could include structural macro-molecules such as lignin, cellulose, suberin and callose in addition to silica and calcium oxalate. Root hairs and rhizosheaths, a structural adaptation unique to grasses, might also play defensive roles. To date, only lignin and silica have been shown to negatively affect root herbivores. In terms of chemical resistance traits, nitrate, oxalic acid, terpenoids, alkaloids, amino acids, cyanogenic glycosides, benzoxazinoids, phenolics and proteinase inhibitors have the potential to negatively affect grass root herbivores. Several good examples demonstrate the existence of indirect defences in grass roots, including maize, which can recruit entomopathogenic nematodes (EPNs) via emission of (E)-β-caryophlyllene, and similar defences are likely to be common. In producing this review, we aimed to equip researchers with candidate root defences for further research.